Seismic retrofit of reinforced concrete beam-column joints using various confinement techniques: A review. (August 2022) - Ong, Chin-Boon; Chin, Chee-Loong; Ma, Chau-Khun; Tan, Jia-Yang; Awang, Abdullah Zawawi; Omar, Wahid
Abstract: The catastrophic seismic events have urged the need for effective retrofitting techniques for the non-seismically designed structures built in the seismic active zone. The design and detailing of beam-column joints are often ignored in early designed structures, thus the retrofit of the beam-column joints is important to ensure the stability of the structures. Over the years, external confinement has emerged to be one of the most effective retrofit techniques. However, several factors have restricted the application of external confinement in practice. These factors include the lack of analysis, design, and confinement scheme guidelines. This paper aims to provide a state-of-the-art review on different confinement techniques that had been proposed to retrofit deficient beam-column joints. The influential parameters, testing method, effectiveness, and reliability of the confinement techniques are critically analysed. The important seismic characteristics of beam-column joint are discussed. Finally, recommendations are provided for future adoption in research and practice.